Analisis Kinerja Bidan pada Pelayanan Antenatal Care di Puskesmas Selayang - Perangin angin, Sri Yunita; Sihombing, Faija; Karo-Karo, Hilda Yani; Rhamawan, Chainny (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Antenatal Care Services (ANC) at the Selayang Health Center, this study used analytic observation research with a "cross-sectional study" design with a sample size of 49 midwives using the formula (Ariawan, 1998 in Yatino, 2005) by conducting interviews and questionnaires. There were 19 respondents who had less knowledge, 47.4% had low performance. The results of the chi-square test obtained a value of p = 0.04 (p <0.05) meaning that Ho was rejected and Ha was accepted, thus there is a relationship between the knowledge factor and the performance of midwives in ANC services. Statistical test results to see the closeness of the relationship obtained the value of Rφ = 0.289 which states that there is a low relationship. Respondents who have less work motivation, 58.3% have low performance, Chi-Square test results obtained ρ = 0.016 which means Ho is rejected Ha is accepted means there is a relationship. The test results for the coefficient φ (phi) obtained Rφ=0.343 which states that there is a low relationship. respondents who stated that the leadership of the puskesmas leaders was quite good, 82.9% had high performance. the results of the statistical test with Chi-Square obtained a value of ρ = 0.00 which means there is a relationship between leadership and performance. The statistical test of the coefficient φ (phi) obtained a value of Rφ = 0.25 which means there is a low relationship. respondents who stated less than the incentives received 50.0% had low performance. Statistical Test with Chi – Square obtained a value of ρ = 0.025 there was a relationship between incentives / rewards on performance. The closeness of the relationship was known by the test results of the coefficient φ (phi) obtained a Rφ = 0.321 there is a low relationship. Respondents who gave a fairly good assessment of their co-workers 20.5% had low performance. Chi – Square obtained the value of ρ = 0.00 The closeness of the relationship is known by the results of the φ coefficient test (phi) obtained by the value of Rφ = 0.433 there is a moderate relationship between colleagues and the performance of midwives in ANC services. Keywords: Factors related to Midwife Performance, ANC Services  ABSTRAK Pelayanan Antenatal Care ( ANC ) di Puskesmas Selayang penelitian ini menggunakan penelitian observasi analitik dengan rancangan “cross sectional study” dengan jumlah sampel 49 bidan dengan menggunakan rumus (ariawan,1998 dalam yatino,2005) dengan melakukan wawancara dan kuesioner. Terdapat 19 responden memiliki pengetahuan kurang 47,4% memilki kinerja rendah. Hasil uji chi-square diperoleh nilai p=0,04 ( p< 0,05) berarti Ho ditolak dan Ha diterima dengan demikian ada hubungan antara faktor pengetahuan dengan kinerja bidan pada pelayanan ANC. Hasil Uji statistik untuk melihat keeratan hubungan diperoleh nilai Rφ = 0,289 yang menyatakan ada hubungan rendah. responden yang memilki motivasi kerja kurang, 58,3% memiliki kinerja rendah, hasil uji Chi- Square diperoleh nilai ρ=0,016 yang berarti Ho ditolak Ha diterima berarti ada hubungan. Hasil uji koefisien φ (phi) diperoleh Rφ=0,343 yang menyatakan ada hubungan rendah. responden yang menyatakan kepemimpinan pemimpin puskesmas Cukup baik, 82,9% memiliki kinerja Tinggi. hasil uji statistic dengan Chi- Square diperoleh nilai ρ=0,00 yang berarti ada hubungan kepemimpinan dengan kinerja, uji statistic koefisien φ (phi) yang diperoleh nilai Rφ = 0,25 berarti terdapat hubungan rendah. responden yang menyatakan kurang terhadap insentif yang diterima 50,0% memilki kinerja rendah, Uji Statistik dengan Chi – Square diperoleh nilai ρ = 0,025 terdapat hubungan antara insentif / imbalan terhadap kinerja, Keeratan hubungan tersebut diketahui dengan hasil uji koefisien φ (phi) diperoleh nilai Rφ = 0,321 terdapat hubungan rendah. responden yang memberikan penilaian cukup baik terhadap rekan kerjanya 20,5% memiliki kinerja rendah. Chi – Square diperoleh nilai ρ = 0,00 Keeratan hubungan tersebut diketahui dengan hasil uji koefisien φ (phi) diperoleh nilai Rφ = 0,433 terdapat hubungan sedang antara rekan kerja dengan kinerja bidan pada pelayanan ANC. Kata Kunci: Faktor- faktor yang Berhubungan dengan Kinerja Bidan, Pelayanan ANC